2018
DOI: 10.1186/s13550-018-0451-z
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical evaluation of PSMA expression in response to androgen receptor blockade for theranostics in prostate cancer

Abstract: BackgroundProstate-specific membrane antigen (PSMA)-directed radioligand therapy (RLT) is a promising yet not curative approach in castration-resistant (CR) prostate cancer (PC). Rational combination therapies may improve treatment efficacy. Here, we explored the effect of androgen receptor blockade (ARB) on PSMA expression visualized by PET and its potential additive effect when combined with 177Lu-PSMA RLT in a mouse model of prostate cancer.MethodsMice bearing human CRPC (C4-2 cells) xenografts were treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
66
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 27 publications
1
66
1
Order By: Relevance
“…Additionally, there was careful consideration of whether or not eligible patients should have progressed on the new‐generation hormone therapies, such as enzalutamide and abiraterone. While there are studies to suggest that there may be a synergistic effect of 177 Lu‐PSMA‐617 therapy with the new‐generation hormonal therapies , this has only been reported in an in vitro and murine model , with anecdotal human data on the efficacy and tolerability of the combination. Thus, for the present study, we felt it was important to establish the comparative activity of the single agent 177 Lu‐PSMA‐617 first, before pursuing other hypotheses of interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, there was careful consideration of whether or not eligible patients should have progressed on the new‐generation hormone therapies, such as enzalutamide and abiraterone. While there are studies to suggest that there may be a synergistic effect of 177 Lu‐PSMA‐617 therapy with the new‐generation hormonal therapies , this has only been reported in an in vitro and murine model , with anecdotal human data on the efficacy and tolerability of the combination. Thus, for the present study, we felt it was important to establish the comparative activity of the single agent 177 Lu‐PSMA‐617 first, before pursuing other hypotheses of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Demonstration of high uptake on 68 Ga‐PSMA‐PET is used for selection of patients for 177 Lu‐PSMA therapy. A number of retrospective studies with substantial variability in treatment regimens have demonstrated favourable PSA responses of >50% in 31–72% of heavily pre‐treated patients with mCRPC .…”
Section: Introductionmentioning
confidence: 99%
“…These results led to a first promising patient report of PSMA upregulation detected by 68 Ga‐PSMA‐11 PET/MRI following 4 weeks of treatment with bicalutamide and a single injection of leuprolide acetate . On the other hand, recently published in vivo data did not show a synergistic treatment effect by using enzalutamide as pretreatment of PSMA‐directed radioligand therapy . Therefore, further research is required to better understand whether short‐term exposure to androgen deprivation therapy might be useful to enhance imaging quality or therapy effects in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…10 On the other hand, recently published in vivo data did not show a synergistic treatment effect by using enzalutamide as pretreatment of PSMAdirected radioligand therapy. 8 Therefore, further research is required to better understand whether short-term exposure to androgen deprivation therapy might be useful to enhance imaging quality or therapy effects in prostate cancer. However, first (bicalutamide) or second (abiraterone, enzalutamide) generation androgen deprivation therapy is associated with relevant side effects in patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation